Effect of Fosroc Cebex-100 and Fly Ash Stabilization on the Microstructural Properties of Soft Soil - Farichah, Himatul; Firmansyah, Yerry Kahaditu; Puspitasari, Nia Dwi; Damayanti, Apta Kania (International Journal of Eco-Innovation in Science and Engineering (IJEISE), 2024)
This study investigates the microstructural effects of stabilizing soft soil using fly ash and Fosroc Cebex-100. The soft soil used in this study was collected from the construction site of the Northern Ring Road (JLU) Section 1 in Lamongan regency. Firstly, a series of laboratory soil test was performed to obtain the index properties of the soil sample including unit weight, specific gravity, Atterberg’s limits, optimum moisture content, and maximum dry unit weight. The soil was then treated with three variations of fly ash (20%, 25%, and 30%), while the Fosroc Cebex-100 dosage was held constant at 0.45% of the fly ash weight. A CBR test indicated that a 20% fly ash and Fosroc Cebex-100 mixture achieved the highest CBR value. Consequently, this optimal mix was selected for SEM-EDX (Scanning Electron Microscopy - Energy-Dispersive X-ray Spectroscopy) analysis to further examine microstructural characteristics. Additional fly ash and Fosroc Cebex-100 to the soft soil will influence the microstructural properties of the soil. SEM analysis show that addition of fly ash and Fosroc Cebex-100 results in significant changes in the soil matrix, including increased particle bonding, reduced porosity, and a denser overall structure. Moreover, the addition of fly ash and Fosroc Cebex-100 contribute to the presence of iron (Fe) in the treated soil.